Redesign of the Foundation for Development of Al Barokah Foundation Flat to Bore Pile Foundation - Era Agita Kabdiyono; Rinaldi Silaban (International Journal Multidisciplinary Science, 2025)
The purpose of redesigning the foundation of the Al Barokah Foundation Apartment into a Bore Pile Foundation is to increase the bearing capacity and ensure structural stability against applied loads. The foundation bearing capacity calculation is based on Standard Penetration Test (SPT) data using the Mayerhoff method on cohesive soil.The results of this research include studying the analysis of changes in deep foundations, soil characteristics, and the foundation's bearing capacity against building loads. The foundation redesign involves using a 60 cm bore pile. For pile cap PC 1, the dimensions are 120 x 120 cm and 60 cm thick. For PC 2, the dimensions are 120 x 120 cm and 60 cm thick, with a concrete quality of fc'=25 MPa. The bore pile reinforcement design for the BP 1 pile foundation is 10D19, with shear reinforcement of D10-52 mm. For the PC 1 pile cap design, the compression main reinforcement in the x- and y-axes is D13-530 mm. For the tension main reinforcement, a diameter of D13-150 mm is used, based on SNI 2847:2019. The foundation settlement value for each pile is the same, at 1.71 cm, which is still within the tolerance limit according to SNI 8460:2017.